Essai historique sur la musique en Russie - Pougin, Arthur 1834-1921 (Turin Bocca, 1897)
"It is not easy, however, to sketch a kind of history of Russian music outside the contemporary period. The present school, so brilliant, so personal, could not have sprung suddenly from the bowels of the earth, and it is not without interest to investigate how it came into being, as a result of what work, what experiments, what attempts. But this is where the embarrassment begins. The general ignorance of the language prevents those who would like to engage in this research from going back to the sources, and I believe that, even in Russia, there is not yet an actual history of national art; at most there are some works, quite numerous in fact, relating either to certain particular chapters of this history, or to some of the artists, contemporary or more or less, who occupy an important place in it." (Source: https://www.babelio.com/livres/Pougin-Essai-historique-sur-la-musique-en-Russie/1226360; Translated with DeepL.com)
Keywords: 19th Century (1801-1900); Music history; Composer; Russia